E-Commerce in Cosmetic Industry - Sonia, D; Hassanah, Hetty (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to find out the brand communication strategy carried out by beauty e-commerce companies in managing the website and how it affects each visitor so that they have a good image. The study used a literature study method with the object of research was the online shop Sociolla and Beautyhaul. The results of this study are the importance of the company to have a good image to communicate brand identity with the trust of consumers and brand or partners. In Indonesia, businesses that specifically sell beauty products online are still relatively rare. Therefore, the company has a big task in conducting brand communication, especially on managing websites because consumers prefer the experience of trying beauty products when buying it directly. The Beauty E-Commerce will facilitate the business in terms of documentation and transactions as well as product offerings in person.